Hospitalization due to traffic accidents among the elderly, Shiraz, 2018; mortality, severity, and injury pattern - Mahnaz Yadollahi; Forough Pazhuheian; Kazem Jamali; Mohammad Hadi Niakan (Archives of Trauma Research, 2020)
Background: Aging results in declined function, which leads to loss of capacity and respond to injury. Hence, the duration of treatment after traffic accident increases in these patients. The present study aimed to identify the factors affecting the elderly hospitalization. Study Design: This was a cross-sectional study. Materials and Methods: This cross-sectional study was conducted on 768 trauma patients aged 65 years and more due to traffic injuries, referred to Rajaee (Emtiaz) hospital trauma referral center, Shiraz, Iran, in 2018. Data were collected through the hospital's health information system, as well as readings and encoding patient's clinical records. Poisson regression was performed to evaluate the partial effects of each covariate on geriatric trauma patients. Results: The mean age of injured patients was 73.27 ± 6.88 years, of which 7.29% expired. Extremities and externals (58.20%) and head and neck (18.36%) were the most commonly injured regions of the body. Each year after 65 led to 0.03 times increase in the length of hospitalization. The male's hospital stay was 1.15 times more than females. Conclusion: According to the results, length of hospitalization had a direct correlation with aging among elderly trauma patients. Since the elderly population is on the rise, it is necessary for the policymakers to come up with preventive measures to reduce the number of accidents and casualties.